PENGEMBANGAN MEDIA INTERAKTIF ANIMASI "PRECISION MATHEMATICS" DALAM PEMBELAJARAN MATEMATIKA ANAK USIA DINI DI TK DHARMA WANITA I GEDANGAN-MALANG - Suratemi, Ririn; Yulia, Nikmahtul Khoir Tri (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2024)
Precision mathematics learning media is adapted to early childhood learning concepts. Aims to describe the mathematics learning process and the results of development in the Interactive Animation media "Precision Mathematics". The type of research method used is the Research and Development (RnD) method with qualitative and quantitative data analysis. Researchers used steps through Borg ang Gall by conducting one product trial in a small group with 10 respondents and a large group with 30 respondents. This research developed the animated interactive media "Precision Mathematics" for children's mathematics learning with 6 material contents, namely number symbols, serialization, classification, one-to-one correspondence, geometry, and subtraction. The results obtained from media experts were 95%. Then, material expert I (media material) got a score of 95%, and material expert II (learning) got a score of 100%. Meanwhile, the results of the small group trial got 66.25%, and the results of the large group got 93%. It can be concluded that the use of the animated interactive media "Precision Mathematics" is very effective for delivering mathematics material to young children. It is hoped that every teacher can choose the right learning media to create fun mathematics learning activities for children.